Barriers to the scientific production of the female university teachers of the Health Sciences areas - Alonso-Arroyo, Adolfo; Gómez-Guardeño, Esperanza; González-Sanjuán, María Eugenia; Aleixandre-Benavent, Rafaél (Faculdade de Filosofia e Ciências, 2013)
To discover the features associated with personal and professional lives of university teachers, in the area of health sciences in the “Comunidad Valenciana” for the period 2003-2007, to learn if they contribute to a greater or lesser scientific productivity. Were interviewed in depth 30 teachers aged between 30 and 60 years in order to identify factors that hamper productivity. Have more difficulties to publish scientific papers, teachers less productive. Represent obstacles: the labor problems, the difficulty to obtain science projects and to publish in certain journals, to balance teaching and research, care work in hospitals, the maternity and children. Although the two groups of large and small producers point to the same problems in their work and personal life, are perceived more difficulties in the group of less productive. Most offer the same kind of solutions to reduce the gender distance.